Involvement of Oligodendrocytes in Tau Seeding and Spreading in Tauopathies - Ferrer, Isidro; Aguiló García, Meritxell; Carmona, Margarita; Andrés-Benito, Pol; Torrejón-Escribano, Benjamin; Garcia-Esparcia, Paula; del Rio, José Antonio (Frontiers in Aging Neuroscience, 2019)
Introduction: Human tau seeding and spreading occur following intracerebral inoculation into different grey matter regions of brain homogenates obtained from tauopathies in transgenic mice expressing wild or mutant tau, and in wild-type (WT) mice. However, little is known about tau propagation following inoculation in the white matter. Objectives: The present study is geared to learning about the patterns of tau seeding and cells involved following unilateral inoculation in the corpus callosum of homogenates from sporadic Alzheimer’s disease and primary tauopathies. Methods: Adult WT mice were inoculated unilaterally in the lateral corpus callosum with sarkosyl-insoluble fractions or with sarkosyl-soluble fractions from the mentioned tauopathies; mice were killed from 4 to 7 months after inoculation. Brains were fixed in paraformaldehyde, embedded in paraffin and processed for immunohistochemistry. Results: Tau seeding occurred in the ipsilateral corpus callosum and was also detected in the contralateral corpus callosum. Phospho-tau deposits were found in oligodendrocytes similar to coiled bodies and in threads. Moreover, tau deposits co-localized with active (phosphorylated) tau kinases p38 and ERK 1/2, suggesting active tau phosphorylation of murine tau. TSAs, GAIs, GOIs, tufted astrocytes, and tau-containing fibrillar astrocytes were not seen in any case. Tau deposits were often associated with slight myelin disruption and the presence of small PLP1-immunoreactive globules and dots in the ipsilateral corpus callosum six months after inoculation of sarkosyl-insoluble fractions from every tauopathy. Conclusions: Seeding and spreading of human tau in the corpus callosum of WT mice occurs in oligodendrocytes, thereby supporting the idea of a role of oligodendrogliopathy in tau seeding and spreading in the white matter in tauopathies. Slight differences in the predominance of threads or oligodendroglial deposits suggest disease differences in the capacity of tau seeding and spreading among tauopathies.